2022
DOI: 10.17826/cumj.1036931
|View full text |Cite
|
Sign up to set email alerts
|

Brain death diagnosis and management in the COVID-19 pandemic

Abstract: Purpose: This present study aimed to share experiences in the diagnosis and management of brain death (BD) and cadaveric donation cases, detected in a research hospital during the COVID-19 pandemic. Materials and Methods: BD cases diagnosed between 15/03/2020-15/05/2021 in our intensive care units (ICU) were retrospectively evaluated. Patients’ demographic characteristics, primary diagnoses, ICU admission time, and length of hospital stay were analyzed. Clinical suspicion, diagnosis, declaration, and don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The primary disease causing permanent brain death in Türkiye has been identified as approximately 50–55% intracranial haemorrhage. [ 8 , 10 , 15 ] In Spain with 1844 cases and in Italy with 1286 cases, the primary disease causing death was found to be intracranial hemorrhage in 56% and 52%, respectively. [ 16 , 17 ] In the study literature, the primary disease of cases with brain death was found to be hemorrhagic cerebral damage in 47% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary disease causing permanent brain death in Türkiye has been identified as approximately 50–55% intracranial haemorrhage. [ 8 , 10 , 15 ] In Spain with 1844 cases and in Italy with 1286 cases, the primary disease causing death was found to be intracranial hemorrhage in 56% and 52%, respectively. [ 16 , 17 ] In the study literature, the primary disease of cases with brain death was found to be hemorrhagic cerebral damage in 47% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in Türkiye, the mean time between admission to intensive care unit and diagnosis of brain death was found to be 2.5–6 days. [ 9 , 10 , 15 , 23 ] In a study conducted in Europe, it was found between 2.5 and 7 days. [ 17 ] In our study, the mean time between admission to the intensive care unit and the diagnosis of brain death was found to be 6 days, consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…118 Finally, a few publications addressed the challenges of apnea testing in patients with COVID-19, which was nonexistent when the WBDP was written. [115][116][117]119,120 Beyond Minimum Clinical BD/DNC Determination…”
Section: New Publications Related To Apnea Testingmentioning
confidence: 99%